Testing for deficient mismatch repair and microsatellite instability: A focused update - Rüschoff, Josef; Schildhaus, Hans Ulrich; Rüschoff, Jan Hendrik; Jöhrens, Korinna; Bocker Edmonston, Tina; Dietmaier, Wolfgang; Bläker, Hendrik; Baretton, Gustavo; Horst, David; Dietel, Manfred; Hartmann, Arndt; Klauschen, Frederick; et al. (Die Pathologie, 2023)
Testing to detect mismatch repair deficiency (dMMR) and high-grade microsatellite instability (MSI-H) has become an integral part of the routine diagnostic workup for colorectal cancer (CRC). While MSI was initially considered to be a possible indicator of a hereditary disposition to cancer (Lynch syndrome, LS), today the prediction of the therapy response to immune checkpoint inhibitors (ICI) is in the foreground. Corresponding recommendations and testing algorithms are available for use in primary diagnosis (reviewed in: Rüschoff et al. 2021).Given the increasing importance for routine use and the expanding indication spectrum of ICI therapies for non-CRCs, such as endometrial, small intestinal, gastric, and biliary tract cancers, an updated review of dMMR/MSI testing is presented. The focus is on the challenges in the assessment of immunohistochemical stains and the value of PCR-based procedures, considering the expanded ICI indication spectrum. A practice-oriented flowchart for everyday diagnostic decision-making is provided that considers new data on the frequency and type of discordances between MMR-IHC and MSI-PCR findings, and the possible role of Next Generation Sequencing in clarifying them. Reference is made to the significance of systematic quality assurance measures (e.g., QuIP MSI portal and multicenter proficiency testing), including regular continued training and education.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Hereditary nonpolyposis colorectal neoplasms; High-throughput nucleotide sequencing; Immune checkpoint inhibitors; Lynch syndrome; MMR immunohistochemistry